(untitled) (The Pakistan Development Review, 2016)
Learning outcomes refer to the performance of the students in academic tests pertaining to the respective grade level. In Pakistan, survey evidences from Annual Status of Education Report (ASER) show a significant dispersion in learning outcomes of public schools as compared with private sector counterpart. The perceived results of learning outcomes in private schools very clear but less evidence is found for educational outcome of schools run under public-private partnership programs. This becomes especially relevant when status of curricular, co-curricular, and extra-curricular activities is compared between public school, private schools, and schools run under public private partnership. In recent literature, it is found that schools taken up by public-private partnership have been providing a better learning environment—Infrastructure Rehabilitation and Development, Administrative changes, Academic Innovation and Planning, Teacher Reform and Student Affairs—is perceived to have a positive impact on learning outcomes. It is to investigate and document that the investments in these areas are justifiable. To promote this fact, we conduct a quasi-experiment to examine the profiles of students in a public-private partnership school at Karachi (running under Zindagi Trust program) and a public school (as counterfactual) in the same neighbourhood. We also recorded the household and socioeconomic characteristics to create a good set of control variables. The propensity-score results show that public-private school is performing better than that of comparison group in attaining learning outcomes thus showing positive effects of PPP. Finally, the study probed into household and parental covariates of student’s educational outcomes to enhance internal validity of results. JEL Classification: I21, C21, L32. Keywords: Educational Learning Outcomes, Public-Private Partnership, Quasi-experiment.